Silicon quantum dot-polyhedral porous carbon composite material and preparation method thereof, lithium ion battery and electric equipment
Through the preparation of silicon quantum dot-polyhedron porous carbon composite materials, the problems of capacity improvement and structural stability of negative electrode materials in lithium-ion batteries are solved, and efficient lithium-ion battery performance is achieved.
Patent Information
- Application Number
- CN202411868968.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
The capacity of the negative electrode material graphite in lithium-ion batteries is close to its theoretical specific capacity, which is difficult to further improve. Moreover, as a substitute material, the volume changes greatly during the charging and discharge process and poor conductivity, which limits its market-oriented development.
Using silicon quantum dot-polyhedral porous carbon composite material, a silicon quantum dot-polyhedral porous carbon is obtained by heating ZIF-8 at high temperature under an inert atmosphere, and then mixing it with silicone and reducing agent and first heating to form a silicon quantum dot-polyhedral porous carbon composite material.
The conductivity and structural stability of the material are improved, the size effect of uniformly dispersed silicon quantum dots slows down the problem of stress concentration, and achieves the high charge and discharge efficiency and long service life of lithium-ion batteries.
Smart Images

Figure CN119650653A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a silicon quantum dot-polyhedron porous carbon composite material and a preparation method thereof, a lithium-ion battery and electrical equipment. Background Art
[0002] Since the Industrial Revolution, the global demand for energy has been increasing day by day. The ecological and environmental problems caused by this have driven researchers to develop clean, sustainable green energy and effective energy storage / conversion systems. Renewable energy, such as solar or wind power, is used to efficiently store it as a chemical energy in reusable batteries or electrochemical capacitors. Lithium-ion batteries (LIBs) embed a large amount of Li in the electrode material. + To store charge, it has excellent properties such as high energy density, high output voltage, low memory effect, long cycle life, etc. It has been widely used in portable electronic devices, drones, robots and electric vehicles.
[0003] Despite the rapid development of LIBs, they still face technical barriers that cannot meet the needs of the future energy market, including low energy density and high cost. From a material perspective, the negative electrode material is one of the key materials in LIBs components. The capacity released by the most widely used commercial graphite negative electrode is close to its theoretical specific capacity (372mAh / g), and it is difficult to continue to increase the capacity. Studies have found that silicon (Si) has a theoretical specific capacity of up to 4200mAh / g and is considered to be the most likely lithium battery negative electrode material to replace graphite. However, Si produces a volume change of up to 300% during the charge and discharge process, which causes its capacity to decay rapidly. In addition, Si itself has poor conductivity, which further hinders its market development.
[0004] In order to solve these problems and accelerate the practical application of Si negative electrodes, various strategies can be used for optimization, such as carbon coating, material nano-sizing, and composite material construction. In recent years, further reducing the size of silicon electrode materials to quantum dot scale has been proven to significantly improve electrochemical performance. In addition, the quantum confinement effect of quantum size can greatly reduce the energy barrier of ion transmission and promote the transport rate of lithium ions. However, silicon quantum dots (SiQDs) have poorer electronic conductivity due to their small size.
[0005] Therefore, it is urgent to propose a new negative electrode material to solve the above problems. Summary of the invention
[0006] The purpose of the present application is to provide a silicon quantum dot-polyhedron porous carbon composite material and a preparation method thereof, a lithium ion battery and an electrical device to solve the above-mentioned problems.
[0007] To achieve the above objectives, the present application provides a first aspect of a method for preparing a silicon quantum dot-polyhedron porous carbon composite material, comprising:
[0008] Under an inert atmosphere, ZIF-8 is heated at high temperature to obtain polyhedral porous carbon;
[0009] The polyhedral porous carbon, organic silicon, a reducing agent and a solvent are mixed and subjected to a first heating to obtain the silicon quantum dot-polyhedral porous carbon composite material.
[0010] Optionally, the preparation method of ZIF-8 comprises:
[0011] The product is prepared by mixing Zn(NO3)2, 2-methylimidazole and methanol and performing a second heating.
[0012] Optionally, the method for preparing the silicon quantum dot-polyhedron porous carbon composite material satisfies at least one of the following conditions:
[0013] A. The mass ratio of Zn(NO3)2 to 2-methylimidazole is 2-5:1;
[0014] B. The second heating temperature is 30°C-80°C and the time is 12h-48h.
[0015] Optionally, the method for preparing the silicon quantum dot-polyhedron porous carbon composite material satisfies at least one of the following conditions:
[0016] A. The organosilicon includes one or more of N-trimethylsilyl imidazole, aminopropyl trimethoxysilane, triphenylsilylamine, diethylenetriaminopropyl trimethoxysilane, and aminopropyl triethoxysilane;
[0017] B. The reducing agent includes one or more of sodium borohydride, ascorbic acid, sodium hypophosphite, sodium thiocyanate, cysteine, citric acid, and sodium citrate.
[0018] Optionally, the method for preparing the silicon quantum dot-polyhedron porous carbon composite material satisfies at least one of the following conditions:
[0019] A. The mass ratio of the organosilicon to the reducing agent is 1-12:1;
[0020] B. The mass ratio of the organic silicon to the polyhedral porous carbon is 0.1-6:1.
[0021] Optionally, the method for preparing the silicon quantum dot-polyhedron porous carbon composite material satisfies at least one of the following conditions:
[0022] A. The high temperature heating temperature is 700℃-1100℃, the heating rate is 2℃ / min-10℃ / min, and the holding time is 2h-24h;
[0023] B. The first heating temperature is 150°C-350°C, and the insulation time is 6h-24h;
[0024] C. The pH value of the solution subjected to the first heating is less than 7.
[0025] The second aspect of the present application provides a silicon quantum dot-polyhedron porous carbon composite material, which is prepared by the preparation method of the silicon quantum dot-polyhedron porous carbon composite material.
[0026] Optionally, the particle size of the silicon quantum dots in the silicon quantum dot-polyhedron porous carbon composite material is 1 nm-30 nm.
[0027] The third aspect of the present application provides a lithium-ion battery, comprising the silicon quantum dot-polyhedron porous carbon composite material.
[0028] A fourth aspect of the present application provides an electrical device comprising the lithium-ion battery.
[0029] Compared with the prior art, the beneficial effects of this application include:
[0030] The preparation method of the silicon quantum dot-polyhedral porous carbon composite material provided in the present application first heats ZIF-8 at high temperature to obtain polyhedral porous carbon, then reduces the silicon element in the silicon source to a suitable valence state by a reducing agent, thereby facilitating its reaction with the carbon source to form a silicon-carbon bond, so that the silicon and the polyhedral porous carbon are tightly combined, and finally the silicon quantum dot-polyhedral porous carbon composite material is prepared by solvent thermal method. The method consists of a simple high-temperature heating reaction and solvent thermal method, and the raw materials are cheap and easy to obtain, the operation is simple and convenient, and the cost is low.
[0031] The silicon quantum dot-polyhedral porous carbon composite material provided in the present application uniformly modifies the silicon quantum dots on the surface or inside of the carbon framework. Due to the high surface energy, some silicon quantum dots electrostatically self-assemble into silicon quantum dot balls. The carbon framework improves the conductivity and structural stability of the material. The size effect of uniformly dispersed silicon quantum dots can effectively alleviate the disadvantage of stress concentration.
[0032] The lithium-ion battery and electrical equipment provided by the present application have high charging and discharging efficiency and long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0034] Figure 1 This is a SEM image of the silicon quantum dot-polyhedron porous carbon composite material prepared in the example. DETAILED DESCRIPTION
[0035] As used herein:
[0036] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0037] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0038] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0039] In these examples, parts and percentages are by mass unless otherwise indicated.
[0040] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0041] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0042] The first aspect of the present application provides a method for preparing a silicon quantum dot-polyhedron porous carbon composite material, comprising:
[0043] Under an inert atmosphere, ZIF-8 is heated at high temperature to obtain polyhedral porous carbon;
[0044] In some embodiments, the inert gas in the inert atmosphere includes argon and / or nitrogen;
[0045] The polyhedral porous carbon, organic silicon, a reducing agent and a solvent are mixed and subjected to a first heating to obtain the silicon quantum dot-polyhedral porous carbon composite material.
[0046] In some embodiments, the solvent comprises water and the first heating is a hydrothermal reaction.
[0047] In some embodiments, the preparation method of ZIF-8 comprises:
[0048] The product is prepared by mixing Zn(NO3)2, 2-methylimidazole and methanol and performing a second heating.
[0049] In some embodiments, the method for preparing the silicon quantum dot-polyhedron porous carbon composite material satisfies at least one of the following conditions:
[0050] A. The mass ratio of Zn(NO3)2 to 2-methylimidazole is 2-5:1;
[0051] Optionally, the mass ratio of Zn(NO3)2 to 2-methylimidazole can be 2:1, 3:1, 4:1, 5:1 or any value between 2-5:1;
[0052] B. The second heating temperature is 30°C-80°C and the time is 12h-48h.
[0053] Optionally, the temperature of the second heating can be 30℃, 40℃, 50℃, 60℃, 70℃, 80℃ or any value between 30℃-80℃, and the time can be 12h, 18h, 24h, 26h, 30h, 34h, 38h, 40h, 44h, 48h or any value between 12h-48h.
[0054] In some embodiments, the method for preparing the silicon quantum dot-polyhedron porous carbon composite material satisfies at least one of the following conditions:
[0055] A. The organosilicon includes one or more of N-trimethylsilyl imidazole, aminopropyl trimethoxysilane, triphenylsilylamine, diethylenetriaminopropyl trimethoxysilane, and aminopropyl triethoxysilane;
[0056] It should be noted that choosing organosilicon as the silicon source for silicon quantum dots has the following advantages:
[0057] ① High reaction activity. The chemical bonds formed by silicon atoms and carbon, hydrogen and other atoms have certain activity. Under the high temperature and high pressure conditions of hydrothermal reaction, a series of chemical reactions, such as hydrolysis and polycondensation, can occur, thereby generating the precursor substances required for silicon-carbon composite materials, which is conducive to the subsequent reactions;
[0058] ② Strong controllability: By selecting organic silicon raw materials with different structures and functional groups, the structure and performance of silicon-carbon composite materials can be regulated. For example, organic silanes containing different organic groups can change the surface properties, pore structure and compatibility with other materials of silicon-carbon materials to meet the performance requirements of silicon-carbon materials in different application scenarios;
[0059] ③Good compatibility with carbon materials: The organic groups in the organosilicon raw materials make them have good compatibility and affinity with carbon materials. During the hydrothermal reaction, the organosilicon can be well adsorbed or bonded to the surface of the carbon material to form a close bond, thereby improving the stability and performance of the silicon-carbon composite material;
[0060] ④High purity and stability: The organic silicon raw materials used for the first heating (hydrothermal reaction) to prepare silicon carbon usually have high purity and good chemical stability. The low impurity content can reduce the interference of impurities on the reaction and the adverse effects on the performance of silicon carbon materials, ensuring the smooth progress of the reaction and the consistency of product performance;
[0061] ⑤ Wide sources: Common organic silicon raw materials can be prepared in large quantities through relatively mature industrial synthesis methods. The sufficient supply of raw materials is conducive to the large-scale industrial production of silicon-carbon materials;
[0062] B. The reducing agent includes one or more of sodium borohydride, ascorbic acid, sodium hypophosphite, sodium thiocyanate, cysteine, citric acid, and sodium citrate.
[0063] It should be noted that the silicon element in the organosilicon silicon source compound is not in a low-valence state suitable for the reaction to generate the target silicon-carbon material. The addition of a reducing agent can reduce the silicon element in the silicon source to a suitable valence state, thereby facilitating its reaction with the carbon source to form a silicon-carbon bond. In addition, there will be some oxidizing substances in the first heating reaction system, which will hinder the normal synthesis of silicon-carbon materials. The reducing agent can consume the oxidizing substances in the system, prevent the silicon source and the carbon source from being oxidized, and ensure that the reaction proceeds in the direction of generating silicon-carbon materials.
[0064] It should also be noted that the synergistic effects of the polyhedral porous carbon, silicone and reducing agent during the first heating reaction are as follows: the silicone raw material can decompose silicon under hydrothermal conditions. The polyhedral porous carbon has a rich pore structure and a large specific surface area, which can provide a place for the deposition of silicon, so that silicon is evenly dispersed in its pores to form a silicon-carbon composite structure, thereby improving the conductivity and structural stability of the material. The reducing agent can reduce the silicon element in the silicone to a suitable low-valent state, making it easier to combine with carbon, promoting the formation of silicon-carbon bonds, enhancing the overall stability of the material, and further stabilizing the silicon-carbon composite structure. The presence of the reducing agent ensures the reducing environment of the reaction system, prevents silicon and carbon from being oxidized, helps to form pure silicon-carbon materials, and improves the electrochemical properties of the material.
[0065] In some embodiments, the method for preparing the silicon quantum dot-polyhedron porous carbon composite material satisfies at least one of the following conditions:
[0066] A. The mass ratio of the organosilicon to the reducing agent is 1-12:1;
[0067] Optionally, the mass ratio of the organosilicon to the reducing agent may be 1:1, 2:1, 4:1, 6:1, 8:1, 10:1, 12:1 or any value between 1 and 12:1;
[0068] B. The mass ratio of the organic silicon to the polyhedral porous carbon is 0.1-6:1.
[0069] Optionally, the mass ratio of the organosilicon to the polyhedral porous carbon can be 0.1:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1 or any value between 0.1-6:1.
[0070] In some embodiments, the method for preparing the silicon quantum dot-polyhedron porous carbon composite material satisfies at least one of the following conditions:
[0071] A. The high temperature heating temperature is 700℃-1100℃, the heating rate is 2℃ / min-10℃ / min, and the holding time is 2h-24h;
[0072] Optionally, the temperature of high temperature heating can be 700°C, 800°C, 900°C, 1000°C, 1100°C or any value between 700°C and 1100°C, the heating rate can be 2°C / min, 4°C / min, 6°C / min, 8°C / min, 10°C / min or any value between 2°C / min and 10°C / min, and the holding time can be 2h, 6h, 10h, 14h, 18h, 22h, 24h or any value between 2h and 24h;
[0073] B. The first heating temperature is 150°C-350°C, and the insulation time is 6h-24h;
[0074] Optionally, the first heating temperature may be 150°C, 200°C, 250°C, 300°C, 350°C or any value between 150°C and 350°C, and the insulation time may be 6h, 10h, 14h, 18h, 24h or any value between 6h and 24h;
[0075] C. The pH value of the solution subjected to the first heating is less than 7.
[0076] Optionally, the pH value of the solution subjected to the first heating may be 1, 2, 3, 4, 5, 6, 6.5, 6.9 or any value less than 7.
[0077] Preferably, the pH value of the solution subjected to the first heating is greater than or equal to 1 and less than 7.
[0078] It should be noted that when the pH value of the solution subjected to the first heating is less than 7, the reducing ability of the reducing agent will be enhanced and can play a better role; the acidic environment can inhibit some possible redox side reactions and make the reduction reaction proceed in the expected direction.
[0079] The second aspect of the present application provides a silicon quantum dot-polyhedron porous carbon composite material, which is prepared by the preparation method of the silicon quantum dot-polyhedron porous carbon composite material.
[0080] In some embodiments, the particle size of the silicon quantum dots in the silicon quantum dot-polyhedral porous carbon composite material is 1 nm-30 nm.
[0081] Optionally, the particle size of the silicon quantum dots in the silicon quantum dot-polyhedral porous carbon composite material can be 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm or any value between 1 nm and 30 nm.
[0082] It should be noted that the main reason for the formation of silicon quantum dots is that MOF has regular, ordered and spatially limited nano-sized pores, which can be used as a microreactor to limit the growth of silicon quantum dots, so that its particle size reaches the quantum dot level, thereby producing a quantum confinement effect and maintaining a stable quantum dot structure; during the solvent thermal reaction, suitable temperature and reducing agent provide energy for the decomposition and reaction of the silicon source, and the solvent affects the diffusion and reaction rate of the silicon source and reaction intermediates, thereby regulating the growth of silicon quantum dots. The unique confined space effect of ZIF-8 and the favorable synthesis conditions work together to make the particle size of silicon quantum dots in the silicon quantum dot-polyhedral porous carbon composite material 1nm-30nm, thereby effectively alleviating the problem of stress concentration.
[0083] The third aspect of the present application provides a lithium-ion battery, comprising the silicon quantum dot-polyhedron porous carbon composite material.
[0084] A fourth aspect of the present application provides an electrical device comprising the lithium-ion battery.
[0085] It should be noted that electrical equipment may be but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.; among them, mobile devices may include but are not limited to at least one of mobile phones, laptop computers, etc.; electric vehicles may include but are not limited to at least one of pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0086] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0087] Example 1
[0088] This embodiment 1 provides a method for preparing a silicon quantum dot-polyhedron porous carbon composite material, and the specific steps include:
[0089] S1. Preparation of ZIF-8:
[0090] Weigh 390g Zn(NO3)2 6H2O and 109g 2-methylimidazole (2-mim) and dissolve them in 500mL methanol respectively, then slowly add the methanol solution of 2-methylimidazole into the methanol solution of Zn(NO3)2 6H2O, and after the mixture is produced, place it in a 60℃ oven for 24 hours to complete the self-assembly process, take it out, cool it naturally to room temperature, and then wash it three times with ethanol by centrifugation for use;
[0091] S2. Preparation of polyhedral porous carbon:
[0092] The synthesized ZIF-8 powder was placed in an alumina boat and pyrolyzed at a temperature of 1000° C. at a heating rate of 3° C. / min under a nitrogen atmosphere with a flow rate of 40 L / min for 1 hour to synthesize a polyhedral carbon framework;
[0093] S3. Preparation of silicon quantum dots-polyhedral porous carbon composite materials:
[0094] Sodium citrate, triphenylsilylamine and the above-synthesized polyhedral porous carbon were dispersed in 60 mL of deionized water in sequence, the pH value of the mixed solution was 5.5, and then transferred into a reactor and kept at 200°C for 6 hours, wherein the mass ratio of sodium citrate to triphenylsilylamine was 1:6, and the mass ratio of triphenylsilylamine to polyhedral carbon was 1:1.
[0095] Among them, the SEM of the silicon quantum dot-polyhedron porous carbon composite material is as follows Figure 1 As shown, silicon quantum dots are uniformly modified on the surface or inside of the carbon framework, with a particle size of 10nm-30nm.
[0096] Example 2
[0097] The difference from Example 1 is that the mass ratio of triphenylsilylamine to polyhedral carbon is 2:1.
[0098] Example 3
[0099] The difference from Example 1 is that the mass ratio of triphenylsilylamine to polyhedral carbon is 3:1.
[0100] Comparative Example 1
[0101] The difference from Example 1 is that only silicon quantum dots are prepared, and the specific steps are as follows:
[0102] Sodium citrate and triphenylsilylamine were dispersed in 60 mL of deionized water in sequence, and then transferred into a reactor and kept at 200° C. for 6 hours to obtain separate silicon quantum dots, wherein the mass ratio of sodium citrate to triphenylsilylamine was 1:6.
[0103] Comparative Example 2
[0104] The difference from Example 1 is that only a polyhedral carbon framework is provided.
[0105] Comparative Example 3
[0106] The difference from Example 1 is that step S3 adopts vapor deposition, and triphenylsilylamine is introduced into a tubular furnace by bubbling nitrogen gas and deposited with the porous carbon skeleton at 450° C. for 10 hours.
[0107] Comparative Example 4
[0108] The difference from Example 1 is that no reducing agent is added.
[0109] The negative electrode materials provided in the above examples and comparative examples were respectively used to prepare batteries, and electrochemical performance tests were performed. The specific test results are shown in Table 1.
[0110] The battery method is specifically as follows: the material, conductive additive carbon black, and adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) are weighed according to a mass ratio of 95:2:3, and placed in a beater at room temperature to prepare a slurry, the prepared slurry is evenly coated on a copper foil, and dried in a blast drying oven at 50°C for 2 hours, and then placed in a vacuum drying oven at 100°C for 8 hours; the negative electrode sheet of the battery is rolled and then transferred into a glove box, and assembled into a CR2032 button battery in a glove box containing a high-purity Ar atmosphere, using metallic lithium as the counter electrode, a solution of 1 mol of LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio v:v=1:1) as the electrolyte, and polyethylene as the diaphragm to assemble into a battery.
[0111] Electrochemical performance test method: Use the Blue Electric test system to perform constant current charge and discharge mode testing, with a discharge cut-off voltage of 0.005V and a charge cut-off voltage of 1.5V. The charge and discharge tests are performed at a current density of C / 10 to test the button battery's charge specific capacity, first-week coulomb efficiency, and capacity retention rate at 500 cycles.
[0112] Table 1 Electrochemical performance test
[0113]
[0114]
[0115] analyze:
[0116] From the comparison of the charge specific capacity data of Examples 1-3 and Comparative Examples 1-2, it can be seen that the size relationship of the charge specific capacity is: Comparative Example 1>Example 1-3>Comparative Example 2, which shows that the quantum-sized silicon material can provide excellent electrochemical properties for the negative electrode material, and the quantum-scale silicon quantum dots have higher lithium storage activity and can provide more ion adsorption active sites.
[0117] From the data comparison of the first-week coulombic efficiency (%) and the capacity retention rate after 500 cycles (%) of Examples 1-3 and Comparative Examples 1-2, it can be seen that their size relationship is: Comparative Example 2>Examples 1-3>Comparative Example 1, which shows that the presence of the porous carbon framework in the composite material can not only improve the intrinsic properties of a single component (such as conductivity), but also the internal cross-linked nanopores can well alleviate the volume effect brought about by the silicon cycle process and enhance the cycle stability.
[0118] From the data comparison of Examples 1-3, it can be seen that ① as the number of silicon quantum dots increases, the specific capacity shows an upward trend, indicating that more silicon quantum dots can provide more lithium storage space; ② as the number of silicon quantum dots increases, the capacity retention rate shows a trend of first increasing and then decreasing, indicating that the structure of silicon quantum dots composite porous carbon should control the content of silicon dots. Although porous carbon can alleviate the volume expansion of silicon and stabilize the structure, a volume expansion of more than 300% will still lead to the collapse of the structure, causing the electrode to fail.
[0119] From the comparison of the charge specific capacity data of Examples 1-3 and Comparative Example 3, it can be seen that the size relationship of the charge specific capacity is: Examples 1-3>Comparative Example 3, indicating that the silicon quantum dot-polyhedron porous carbon composite material prepared by the present application is more advantageous than the silicon-carbon material prepared by the conventional vapor deposition method. This indicates that the preparation method of the present application avoids the problems of material agglomeration and structural damage that occur in high-temperature vapor deposition, thereby allowing the material to exert a greater specific capacity.
[0120] From the comparison of the charge specific capacity data of Examples 1-3 and Comparative Example 4, it can be seen that the size relationship of the charge specific capacity is: Examples 1-3>Comparative Example 4, which shows that the presence of the reducing agent can make more silicon sources available, further emphasizing the importance of the reducing agent in the reaction system.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0122] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a silicon quantum dot-polyhedron porous carbon composite material, characterized in that: include: Under an inert atmosphere, ZIF-8 is heated at high temperature to obtain polyhedral porous carbon; The polyhedral porous carbon, organic silicon, a reducing agent and a solvent are mixed and subjected to a first heating to obtain the silicon quantum dot-polyhedral porous carbon composite material.
2. The method for preparing the silicon quantum dot-polyhedron porous carbon composite material according to claim 1, characterized in that: The preparation method of ZIF-8 comprises: The product is prepared by mixing Zn(NO3)2, 2-methylimidazole and methanol and performing a second heating.
3. The method for preparing the silicon quantum dot-polyhedron porous carbon composite material according to claim 2, characterized in that: At least one of the following conditions is met: A. The mass ratio of Zn(NO3)2 to 2-methylimidazole is 2-5:1; B. The second heating temperature is 30°C-80°C and the time is 12h-48h.
4. The method for preparing the silicon quantum dot-polyhedron porous carbon composite material according to claim 1, characterized in that: At least one of the following conditions is met: A. The organosilicon includes one or more of N-trimethylsilyl imidazole, aminopropyl trimethoxysilane, triphenylsilylamine, diethylenetriaminopropyl trimethoxysilane, and aminopropyl triethoxysilane; B. The reducing agent includes one or more of sodium borohydride, ascorbic acid, sodium hypophosphite, sodium thiocyanate, cysteine, citric acid, and sodium citrate.
5. The method for preparing the silicon quantum dot-polyhedron porous carbon composite material according to claim 1, characterized in that: At least one of the following conditions is met: A. The mass ratio of the organosilicon to the reducing agent is 1-12:1; B. The mass ratio of the organic silicon to the polyhedral porous carbon is 0.1-6:
1.
6. The method for preparing the silicon quantum dot-polyhedron porous carbon composite material according to any one of claims 1 to 5, characterized in that: At least one of the following conditions is met: A. The high temperature heating temperature is 700℃-1100℃, the heating rate is 2℃ / min-10℃ / min, and the holding time is 2h-24h; B. The first heating temperature is 150°C-350°C, and the insulation time is 6h-24h; C. The pH value of the solution subjected to the first heating is less than 7.
7. A silicon quantum dot-polyhedron porous carbon composite material, characterized in that: The silicon quantum dot-polyhedron porous carbon composite material is prepared by the preparation method of any one of claims 1 to 6.
8. The silicon quantum dot-polyhedron porous carbon composite material according to claim 7, characterized in that: The particle size of the silicon quantum dots in the silicon quantum dot-polyhedron porous carbon composite material is 1nm-30nm.
9. A lithium ion battery, characterized in that: It includes the silicon quantum dot-polyhedron porous carbon composite material as described in claim 7 or 8.
10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.